EFEKTIVITAS PPL II SECARA DARING DALAM KESIAPAN MAHASISWA MENJADI GURU DI FKIP ULM (Studi Kasus Mahasiswa Pendidikan Ekonomi Angkatan 2018) - Raihanah Sari; Mahmudah Hasanah (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Education plays a very important role in the process of improving the quality of human resources. Improving the quality of education is a process that is integrated with the process of improving the quality of human resources. One of the efforts to prepare the ability of prospective teachers in facing learning tasks, can be done through the Field Experience Program (PPL) and also a program which is a training event to determine the various knowledge, attitudes, and skills of teachers, they can carry out their duties and responsibilities independently. professionals, as well as the framework of the formation of professional teachers. Online learning activities carried out by FKIP ULM students during the PPL II implementation in the 2021/2022 academic year are assisted by applications such as zoom and google meet. Judging from the results of a survey conducted by the author to economic education students, what happened in the field of implementing PPL online, in fact, it still can't be said to be maximal in its implementation, because many students complain such as inhibiting factors for online learning activities carried out by students, factors that hinder the implementation of PPL such as quotas, networks, inadequate devices from students and from students themselves and also online learning platform media that are still underutilized by teachers or students, resulting in difficulty in conducting learning interactions between students and teachers or students in the learning process. Therefore, it is very necessary for students to have the readiness to become teachers, both online and offline.